Activated carbons synthesized from unaltered and pelletized biomass wastes for bio-tar adsorption in different phases. (February 2020) - Shen, Yafei; Zhou, Yuewei; Fu, Yuhong; Zhang, Niyu
Abstract: The activated carbons were synthesized from rice husk (RH) and rice husk pellet (RHP) by the two-step pyrolysis (carbonization followed by KOH activation). Based on their textural properties, the activated carbons were comparatively studied for sorption of phenol (tar model compound) in different phases. The surface area (SBET ) and pore volumes of RH and RHP chars could be significantly improved with increasing the amount of KOH. Particularly, the RH char-3 showed a highest SBET (1818.45 m 2 /g) with a higher micro-porosity (93.3%), so the KOH activation of RH char favored the development of microporous structures. Compared with the RH char-3, the RHP char-3 with relatively low SBET (1320 m 2 /g) showed a meso-microporous structure along with a lower micro-porosity (69.2%), contributing to a higher breakthrough adsorption capacity (740 mg/g) of gaseous phenol. Generally, the adsorption capacity of phenol in the gas phase was higher than that in the liquid phase. RHP favored to form the hierarchical porous carbon enhancing the phenol molecules transportation via the outer layer and then the phenol molecules uptake by the adsorption sites on the inner layer. Also, the appropriate moisture in biochar benefited for adsorption, while the excessive water formed the liquid film, controlling the molecules transport. Graphical abstract: Image 1 Highlights: Activated carbons were synthesized from the unaltered and pelletized rice husk. The maximum specific surface area (SBET ) can reach about 1818 m 2 /g. The pelletized rice husk favored to form the meso-microporous carbons enhancing the adsorption. The maximum breakthrough adsorption capacity of phenol in the gas phase can reach 740 mg/g. The adsorption capacity of phenol in gas was much higher than that in liquid.